PENGEMBANGAN MODUL MATEMATIKA BERBASIS MASALAH PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Suprihatiningsih, Siti; Annurwanda, Pradipta (Universitas Muhammadiyah Semarang, 2019)
This study aims to develop a problem-based mathematical module in the material system of two-variable linear equations of class VIII SMP students that are valid, practical and effective. This research is a development research with the method used is ADDIE. The subject of this study was the eighth grade students of SMP Negeri 1 Ngabang, Landak District. The instruments used were validation sheets, observation sheets and student learning outcomes tests. The result indicates that a problem-based mathematical module has been developed in the material system of two-variable linear equations of class VIII SMP students that are valid, practical and effective. Based on the results of the validity test, it can be stated that the problem-based mathematical module produced is valid with a validity value of 79.11. The implementation observation results show that the problem-based mathematics module is in the practical category with a practical value of 82.18. Then the results of student learning tests showed that the average value of the learning outcomes test was 83.00 and the effectiveness of the problem-based mathematics module was 87.50% and included in the effective category. When viewed from the results of the tests performed, the development of problem-based mathematical modules in the subject matter of the two-variable linear equation system has been successfully developed and is suitable for use in Ngabang 1 State Middle School.